2016
DOI: 10.18632/oncotarget.13980
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA16 is a potential biomarker for diagnosis of early-stage lung cancer that promotes cell proliferation by regulating the cell cycle

Abstract: Early diagnosis of lung cancer greatly reduces mortality; however, the lack of suitable plasma biomarkers presents a major obstacle. Recent studies showed that long noncoding RNAs (lncRNAs) played important roles in cancer initiation and development. Here, we identified differentially expressed lncRNAs in 20 lung cancer samples by using custom designed microarray and evaluated their expression in 118 lung cancer samples by real-time PCR (qRT-PCR). lncRNA16 (ENST00000539303) expression was significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In breast cancer, SNHG16 is positively associated with increased proliferation rate, apoptosis evasion, and cell cycle progression through ceRNA binding of miR-98, followed by E2F5 up-regulation (172). Moreover, this lncRNA also has the potential to become a biomarker of early-stage pulmonary malignancy, which is very difficult to diagnose with currently available methods (173). In ovarian cancer, SNHG16 increases malignant cell migration capacity through phosphorylationmediated activation of AKT (AKT serine/threonine kinase 1) and overexpression of MMP9 (174).…”
Section: Small Nucleolar Rna Host Gene 16 (Snhg16)mentioning
confidence: 99%
“…In breast cancer, SNHG16 is positively associated with increased proliferation rate, apoptosis evasion, and cell cycle progression through ceRNA binding of miR-98, followed by E2F5 up-regulation (172). Moreover, this lncRNA also has the potential to become a biomarker of early-stage pulmonary malignancy, which is very difficult to diagnose with currently available methods (173). In ovarian cancer, SNHG16 increases malignant cell migration capacity through phosphorylationmediated activation of AKT (AKT serine/threonine kinase 1) and overexpression of MMP9 (174).…”
Section: Small Nucleolar Rna Host Gene 16 (Snhg16)mentioning
confidence: 99%
“…Long non‐coding RNA (lncRNA) are a class of regulatory non‐coding RNAs molecules and are more than 200 nucleotides in length; they have been identified to play crucial roles in regulating gene expression during tumor progression (Chen et al, ; Li, Zhang, et al, ; Lv et al, ; Zhu et al, ). An increasing number of studies have shown that the aberrant expression of HOTAIR is associated with glioma genesis and that HOTAIR participates in different biological processes in glioma; for example, Zhang et al () reported that HOTAIR promotes glioblastoma cell cycle progression in an EZH2‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), was found to be a good predictor for HCC recurrence after liver transplantation 30 . lncRNA 16 (ENST00000539303) and Sox2 overlapping transcript (Sox2ot) were reported to be associated with prognosis in patients with lung and gastric cancers, respectively 31, 32 .…”
Section: Discussionmentioning
confidence: 99%